Strategie kontroli i represji Kościoła scjentologicznego wobec amerykańskiej kinematografii - PIGULAK, MARCIN (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
The Church of Scientology’s strategies of control and repression of towards American cinema The aim of this article is to show the strategies of control developed by the Church of Scientology and repressions enforced by the Church on representatives of American cinema, who through their artistic work entered the current of criticism of this organization. By describing the beginnings of this religious movement, which includes indicating the sources of the very first contacts with the world of Hollywood, the article presents the role which celebrities played in promoting scientology and as a medium of religious values. Similarly, by listing the most important examples of Scientologys oppressiveness towards its opponents, the author points to the close correlation with the fundamental ideas developed by its founder. The author of this article concentrates on selected instances of Church interference and in doing so describes the history of this organizations influence on the American film-making milieu, as well as ascribing selected anti-Scientology films to the trend of broader opposition towards Scientologists’ activities.